Commentary on the Old Testament ; v. 8 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Patrick, David; Kennedy, James (Grand Rapids, MI Eerdmans)
Contents : v. 8 : Jeremiah, Lamentations / C.F. Keil. Includes bibliographical references.
Reprinted 1975.
Keywords: Bible. O.T. -- commentaries